Laboratory Notes, Laboratory Experiences, and Conceptual Analysis: Understanding the Making of Ohm's First Law in Electricity. Issue 1 (16th March 2020) - Heering, Peter; Keck, Julian; Rohlfs, Gerhard A.
Abstract: Georg Simon Ohm's work in the field of electricity led to what is now considered to be the most fundamental law of electrical circuits, Ohm's Law. Much less known is that only months earlier, Ohm had published another law—one that differed significantly from the now accepted one. The latter entailed a logarithmic relation between the length of the conductor and a parameter that Ohm called "loss of force." This paper discusses how Ohm came up with an initial law that he felt compelled to correct a few months later. We analyze Ohm's publication as well as his laboratory notes, relating them to our own laboratory experiences while using the replication method to study his work. We also discuss the conceptual background of Ohm's work. We conclude that he was significantly influenced by French studies in the field of electricity, most notably the ones by Charles Augustin Coulomb.